Risk Factors for Nonalcoholic Fatty Liver Disease in Patients Presenting to Medical Unit of Secondary Healthcare Facility - Khan, Shah Zaib Alam; Mumtaz, Arif (Biological and Clinical Sciences Research Journal, 2025)
Non-alcoholic fatty liver disease (NAFLD) is increasingly prevalent and drives substantial metabolic and cardiovascular morbidity. Early recognition of context-specific risk factors is crucial, especially in secondary-care settings with high patient throughput.. Objective: To determine the risk factors for nonalcoholic fatty liver disease in patients presenting to the medical unit of a secondary healthcare facility. Methodology: Two hundred thirty patients aged 25 to 70 years diagnosed with NAFLD based on clinical symptoms such as jaundice, dark urine and itchy skin along with ultrasonographic findings were enrolled. Patients with other liver diseases were excluded. Data on demographics and risk factors were obtained. Risk factors assessed in our study were diabetes, hypertension, obesity and thyroid dysfunction. SPSS 27 was utilized for analysis. Results: The mean age of our 230 patients was 48.13±13.31 years with mean BMI 29.18±2.53 kg/m². The study population was mostly male (58.7%). A majority of patients were from lower and middle socioeconomic background (39.1% and 41.3% respectively). Regarding the risk factors diabetes was 56.1% and hypertension 52.2%, followed by obesity 40.9% and thyroid dysfunction 12.6%. Statistical analysis showed that diabetes and hypertension were associated with older age groups. Thyroid dysfunction showed a potential association with female gender and lower socioeconomic status. Conclusion: Diabetes, hypertension, obesity and thyroid dysfunction are the leading risk factors for NAFLD. Associations were found for diabetes and hypertension with increasing age, while thyroid dysfunction showed an association with female gender.